1994
DOI: 10.1093/nar/22.10.1866
|View full text |Cite
|
Sign up to set email alerts
|

Removal of 3′-phosphoglycolate from DNA strand-break damage in an oligonucleotide substrate by recombinant human apurinic/apyrimidinic endonuclease 1

Abstract: A recombinant human AP endonuclease, HAP1, was constructed and characterized with respect to its ability to recognize and act upon a model double-stranded 39-mer oligodeoxyribonucleotide substrate containing a strand break site with 3'-phosphoglycolate and 5'-phosphate end-group chemistries. This oligodeoxyribonucleotide substrate exactly duplicates the chemistry and configuration of a major DNA lesion produced by ionizing radiation. HAP1 was found to recognize the strand break, and catalyze the release of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 24 publications
4
59
0
Order By: Relevance
“…Our findings are consistent with the reports of others showing that APE1 is able to remove 3' phosphates Seki et al 1992;Winters et al 1994), 3' phosphoglycolates (Suh et al 1997), and 3' tyrosyl groups , importantly, under a wide variety of assay conditions. Thus, although the in vitro 3' to 5' exonuclease activity of APE1 is approximately 300-fold lower than its AP endonuclease activity, the data in total argue that APE1 is a likely candidate to remove 3' phosphates, phosphoglycolates, and tyrosyl residues during relevant DNA repair processes, particularly in comparison to the other human exonucleases examined here.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with the reports of others showing that APE1 is able to remove 3' phosphates Seki et al 1992;Winters et al 1994), 3' phosphoglycolates (Suh et al 1997), and 3' tyrosyl groups , importantly, under a wide variety of assay conditions. Thus, although the in vitro 3' to 5' exonuclease activity of APE1 is approximately 300-fold lower than its AP endonuclease activity, the data in total argue that APE1 is a likely candidate to remove 3' phosphates, phosphoglycolates, and tyrosyl residues during relevant DNA repair processes, particularly in comparison to the other human exonucleases examined here.…”
Section: Discussionsupporting
confidence: 93%
“…These include apurinic/apyrimidinic endonuclease 1 (APE1), three prime repair exonuclease (TREX1), the damage response tumor suppressor protein p53, and Werner syndrome protein (WRN). APE1 is the major AP endonuclease, but also contributes to the repair of 3'-phosphates, -phosphoglycolates, -tyrosyl groups, and -mismatched nucleotides (Demple and Harrison 1994;Winters et al 1994;Suh et al 1997;Chou and Cheng 2002;Hadi et al 2002;. TREX1, originally designated DNase III, was isolated as the major nuclear, DNA-specific 3' to 5' exonuclease (Hoss et al 1999;Mazur and Perrino 1999;Mazur and Perrino 2001b).…”
Section: Introductionmentioning
confidence: 99%
“…Although an APE1 knock-out produces embryonic lethality in (Xanthoudakis et al, 1994), antisense experiments showed that Ape1 makes a significant contribution to cellular resistance to oxidative damage (Ono et al, 1994;Walker et al, 1994), in line with a role in repair of 3'-PG and other oxidative lesions. More recently, the ability of Ape1 to excise 3'-PG was confirmed in vitro (Chaudhry et al, 1999;Winters et al, 1994), and an adaptive response has been described in which the induction of Ape1 expression plays a critical role (see Cellular modulation of BER for oxidative damage). Recently, Mitra and colleagues showed that Ape1 carries out the ratelimiting step in 3'-PG repair (Izumi et al, 2000).…”
Section: The Biology Of Oasmentioning
confidence: 94%
“…It is interesting that the time course of ssb repair, measured in parallel (not shown), was even slower than the repair of d-pNpg, indicating that the latter process does not constitute the rate limiting step for strand break repair. Several activities of 3'-pg removal in eukaryotic cells have been reported aim (48,49). In one case the mechanism of 3'-phosphoglicolate removal was investigated with a purified recombinant abasic endonuclease.…”
Section: Discussionmentioning
confidence: 99%
“…In one case the mechanism of 3'-phosphoglicolate removal was investigated with a purified recombinant abasic endonuclease. It was shown that the enzyme releases phosphoglycolate and phosphate from 3'-pg and 3'-p respectively (49).…”
Section: Discussionmentioning
confidence: 99%